Role of speckle tracking echocardiography in patients with myocardial infarction - A. V. Kobets; M. P. Kopytsia; N. V. Tytarenko; Yu. V. Rodionova (Patologìâ)
All over the world cardiovascular diseases are one of the main reason of morbidity and mortality in the structure of non-communicable diseases, and myocardial infarction has a leading role. Markers of modern advanced ultrasound techniques, speckle tracking echocardiography, play significant role in the detection and assessment of cardiovascular disease. Deviation of them can detect myocardial ischemia, hypertrophy, dystrophy and infiltration, severe systemic diseases, cardiotoxicity of the drugs, etc.